SOSIALISASI WAWASAN KEBANGSAAN SEBAGAI UPAYA PENGUATAN KETAHANAN NASIONAL INDONESIA - Isabella Isabella (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
In the community, nation and state, today is experiencing with the times. Indonesia as a country with a vast territory and a population has also changed significantly in many sectors. These changes will certainly bring influence on the dynamic state of this country with regard to ductility, and toughness needed to develop strength and ability to address all threats, challenges and interference both from within and outside. This condition is called national resilience. Therefore, we need a strategy that is appropriate for the current condition so that national resilience of Indonesia can be implemented, protected and maintained. The strategy is also important to produce strength and care for the interest of Indonesia. The number of cases of abuse against symbols of the state, the lack of knowledge of younger generation towards the concept of nationalism are two examples of this nation’s problems. One of the efforts made by the House of Representatives in the MPR, DPR and DPRD in cultivating national security is through socialization of national insight. The socialization of national insight would make a positive contribution to the national resilience of Indonesia. The success of this socialization can be seen from the efforts that have been made so far.Key words: national resilience, socialization of national insight, students